Use of different imaging techniques in stab wound analysis - Bergman, Linnea; Brock, Fiona; Errickson, David (Elsevier, 2023)
Stab wound analysis is a relatively new field of study in forensic science, and there is currently much debate regarding the effectiveness of the analysis due to a lack of validation studies. Furthermore, the underlying viewpoints on the success of stab wound analysis vary. Examination of cut marks, for example, can reveal a variety of characteristics which can be used to determine the type of weapon that was used to inflict them. However, published studies are not consistent when identifying knife blade characteristics, instead considering a wide variety of morphological aspects and their potential value in forensic scenarios. The existing research methodology is therefore inadequate to reliably inform in such contexts, and future experimental design should be influenced by the conditional variance in stabbings in order to provide reliable findings. The research presented here takes a systematic approach to the problem, compiling the published literature (up to September 2023) on the use of different imaging methods applied to stab wound examination to create a taxonomy to examine trends in methodological approaches in both research and investigative settings. This approach identified that published studies could be classified as either morphological or morphometrical, and further sub-classified based on their degree of success and the findings reached. This emphasises the importance of prioritising research into mark data, and the need for a multi-technique, multi-disciplinary approach. A decision tree was created to illustrate which mark attributes should be studied for which purpose, and using which imaging method(s). Furthermore, the research presented identifies two key areas in stab wound research which should be the focus of standardisation efforts, namely methodological procedures and mark characteristic collection. Knife markings are difficult to interpret, but further research and standardisation of kerf mark analysis, as highlighted here, will improve the efficiency and reliability of both forensic investigations and future experimental studies.
Keywords: Stab wound analysis; Imaging methods; Kerf marks; CT; Micro-CT; Scanning electron microscope